2005
DOI: 10.1002/humu.9382
|View full text |Cite
|
Sign up to set email alerts
|

The first missense alteration in the MCPH1 gene causes autosomal recessive microcephaly with an extremely mild cellular and clinical phenotype

Abstract: Autosomal recessive primary microcephaly (MCPH) is a rare neurodevelopmental disorder characterized by mental retardation and congenital microcephaly with a head circumference at least 4 SD below age and sex means, in the absence of other significant malformations or neurological deficits. Truncating alterations in the MCPH1 gene have previously been shown to exhibit a distinct cellular phenotype, with a high proportion of prophase-like cells (>10%) due to premature chromosome condensation in early G2-and dela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 20 publications
1
44
0
Order By: Relevance
“…4,[12][13][14][15][16] In parallel, it was shown that other MCPH patients with mutations in ASPM (MCPH5) or WDR62 (MCPH2) can also exhibit ACC and that a patient with microcephaly harboring a missense in the Microcephalin gene (MCPH1) presented a less severe clinical phenotype compared with the patients with truncating mutations in the same gene. [17][18][19] We might therefore propose that mutations completely abolishing CDK5RAP2 protein function, such as nonsense or frameshift mutations, would lead to a microcephaly phenotype, whereas recessive missense mutations, where there may be some residual function, might result in a different phenotype such as isolated ACC. This is the first time that recessive missense mutations in CDK5RAP2 are specifically associated with corpus callosum anomalies, a finding which provides new avenues to a better understanding of the role of the centrosome into early development of corpus callosum.…”
Section: Discussionmentioning
confidence: 99%
“…4,[12][13][14][15][16] In parallel, it was shown that other MCPH patients with mutations in ASPM (MCPH5) or WDR62 (MCPH2) can also exhibit ACC and that a patient with microcephaly harboring a missense in the Microcephalin gene (MCPH1) presented a less severe clinical phenotype compared with the patients with truncating mutations in the same gene. [17][18][19] We might therefore propose that mutations completely abolishing CDK5RAP2 protein function, such as nonsense or frameshift mutations, would lead to a microcephaly phenotype, whereas recessive missense mutations, where there may be some residual function, might result in a different phenotype such as isolated ACC. This is the first time that recessive missense mutations in CDK5RAP2 are specifically associated with corpus callosum anomalies, a finding which provides new avenues to a better understanding of the role of the centrosome into early development of corpus callosum.…”
Section: Discussionmentioning
confidence: 99%
“…3B). A recent report describes a missense mutation in the N-BRCT domain that changes a conserved Thr to Arg (T27R) in the BRCT domain (26). What is interesting is that the patient had a mild clinical and cellular phenotype compared with known mutant alleles of MCPH1 that are truncating mutations.…”
Section: Discussionmentioning
confidence: 99%
“…We also did not observe any defect in the process of chromosome condensation comparable to the cellular phenotype caused by MCPH1 mutations. 25,33 The cell cycle progression and the spindle checkpoint activity in MCPH8 patient cells was analyzed by FACS on both lymphoblastoid cells and PHA stimulated T-lymphocytes. Cells were arrested in mitosis for 12 h with nocodazole, a microtubule-depolymerizing agent and subsequently released from mitosis during either 30 min or 2 h. Mitotic indices and DNA profiles were evaluated in order to detect the response of cells to metaphase arrest caused by nocodazole.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%